Constitution of Sierra Leone - Government of Sierra Leone (1991)

Mother Tongue Education: The West African Experience - Bamgbose, Ayo (Hodder and Stoughton Ltd, 1976)
In the rapidly changing political, economic, and social life of West Africa, there is a renewed interest in cultural identity. This book describes the developments and the difficulties experienced by different West African countries in the use of mother tongues in multi-lingual society. The book was commissioned to give scholars, educators, and policy-makers concerned with mother tongue education an account of developments in selected countries. Three broad areas are covered: (1) situations where the mother tongue has not yet been introduced into the formal school system but where preparations are being made; (2) situations where there has been a long tradition of mother tongue education; and (3) special projects. An introduction discusses the role of the mother tongue in education, with particular reference to West Africa. This is followed by a historical sketch of developments in mother tongue education. Contributions from Sierra Leone and Dahomey cover the first of the areas mentioned. Ghana's report covers the second area. The last two reports, from Nigeria, fall into the third category. Finally, two projects are described: the Six-Year Primary Project on the use of a major language as a medium of instruction and the Rivers Readers Project on the introduction of smaller languages into the formal school system. (Author/AM)
Keywords: African Culture; African Languages; Bilingual Education; Educational Planning; French; Igbo; Language Planning; Language of Instruction; Mandingo; Mende; Multilingualism; Native Speakers; Portuguese; Regional Dialects; Sociolinguistics; Susu; Uncommonly Taught Languages; Wolof; Yoruba